2005
DOI: 10.1200/jco.2005.08.140
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells: A Novel Prognostic Factor for Newly Diagnosed Metastatic Breast Cancer

Abstract: Detection of CTCs before initiation of first-line therapy in patients with MBC is highly predictive of PFS and OS. This technology can aid in appropriate patient stratification and design of tailored treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
688
1
22

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,028 publications
(745 citation statements)
references
References 15 publications
24
688
1
22
Order By: Relevance
“…This hypothesis was confirmed by several studies which found a strong correlation between the level of circulating tumor cells (CTCs) and the prognosis of metastatic breast cancer by showing that the number of circulating tumor cells before treatment is an independent predictor of overall survival in patients with metastatic breast cancer [25][26][27]. Also patients who after treatment converted from elevated CTCs to nonelevated levels show a clinical response [28].…”
Section: Total (95% Ci)mentioning
confidence: 73%
“…This hypothesis was confirmed by several studies which found a strong correlation between the level of circulating tumor cells (CTCs) and the prognosis of metastatic breast cancer by showing that the number of circulating tumor cells before treatment is an independent predictor of overall survival in patients with metastatic breast cancer [25][26][27]. Also patients who after treatment converted from elevated CTCs to nonelevated levels show a clinical response [28].…”
Section: Total (95% Ci)mentioning
confidence: 73%
“…Assessment of CTC using CellSearch has been cleared by the Food and Drug Administration as a prognostic indicator, in conjunction with other clinical methods, for patients with metastatic breast, prostate, and colorectal cancers. Studies in metastatic breast, colorectal, and prostate cancer showed that patients about to start new lines of chemotherapy could be divided into groups with favourable and unfavourable prognosis on the basis of the number of CTCs measured with the analytically valid CellSearch system(Veridex, Raritan, NJ, USA) [3,[5][6][7][8][9][10][11][12][13]20]. When studying the association between the number of CTCs and evolution of the disease, researchers generally use a single cutpoint to identify favorable and unfavorable response groups, such as 5 CTCs for MBC [3,4,14], three for metastatic colorectal cancer [11], and five for castration resistant prostate cancer [7].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating tumor cells (CTCs) have been shown to be an independent prognostic factor in metastatic breast cancer (MBC) [3][4][5][6], in metastatic prostate cancer [7][8][9][10] and in metastatic colorectal cancer [11,12]. They represent a promising tool for therapeutic monitoring: an elevated number of CTCs measured at any time in the clinical course were associated with a high likelihood of a very short time to progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several assays to detect CTCs have been introduced [3]. CTCs measured with the FDA-approved CellSearch technique (Veridex™, Raritan, NJ) have prognostic value in metastatic breast cancer [4,5] and changes in CTC counts during systemic therapy can serve as early marker for response [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%